Targeted electronic health record-based recruitment strategy to enhance COVID-19 vaccine response clinical research study enrollment - Hninn Khine; Alex Mathson; Puleng R. Moshele; Bharat Thyagarajan; Amy B. Karger; Stefani N. Thomas (Contemporary Clinical Trials Communications, 2024)
Efficient recruitment of eligible participants is a significant challenge for clinical research studies. This challenge was exacerbated during the COVID-19 pandemic when in-person recruitment was not an option. In 2020, the University of Minnesota was tasked, as part of the National Cancer Institute's Serological Sciences Network for COVID-19 (SeroNet), to recruit participants for a longitudinal serosurveillance clinical research study with a goal of characterizing the COVID-19 vaccine-elicited immune response among immunocompromised individuals, which necessitated reliance on non-traditional strategies for participant recruitment. To meet our enrollment target of 300 transplant patients, 300 cancer patients, 100 persons living with HIV, and 200 immunocompetent individuals, we utilized targeted electronic health record (EHR)-based recruitment in addition to traditional recruitment tools, which was an effective combination of recruitment strategies. A significant advantage of patient portal messaging or other digital recruitment strategies such as email communication is timing. We reached 85 % (769 out of 900) of our enrollment target within one year with a 14.3 % response rate to invitations to participate in our study. This achievement is perhaps more salient given the COVID-19 pandemic-related constraints within which we were operating. We demonstrated that the EHR can be leveraged to quickly identify potentially eligible study participants either via EHR communication or mail. We also illustrate how the online portal MyChart can be used to efficiently send targeted recruitment messages.